Interpretation of Disruptive Innovation in the Era of Smart Cities of the Fourth Industrial Revolution - Gábor Nick; Ferenc Pongrácz; Edit Radács (DETUROPE)
The exponential development of information technology and, in this context, the latest generation of open innovation systems result in revolutionary changes in almost every industry as well as in other areas of life. From the automotive industry to the energy sector and to tourism, newcomers emerge everywhere, building on the tools of disruptive innovation, which with earlier unprecedented speeds transform their previous industry power. The essence of the smart city approach is to put the latest tools of technological advancement in serving the social, economic and ecological sustainability of cities' lives for the inhabitants as well as for the enterprises of the city. Industry 4.0 is an imagined future, which in our opinion – in direct or indirect ways – would have a fundamental influence on smart cities and their environment and regions, given that their primary goal is to improve a country's competitiveness. In our study, we review the relevant literature on the definition of and approach to innovation as well as the smart city concept in this new revolutionary age, we demonstrate relevant correlations between the concepts of disruptive innovation, smart city and Industry 4.0